How to boost your cataract surgical rates during pandemic covid-19: Poster Presentation - Observational Study - Ophthalmologist - Kusuma, Hendra; Armada, Dhani; Kumala, Marissa Mutiara (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Cataracts are the number one cause of blindness in the world and a big burden in Indonesia. The Covid-19 pandemic has caused the cessation of health services to eradicate blindness (cataract lock down). This article discusses how to develop eye care services in one of the red zones of blindness in South Sulawesi, specifically in Jeneponto district during the Covid-19 pandemic. Methods : Observational research Results : Establishment of a safety protocol that is implemented and promoted to the public continuously, especially through social media, was able to increase trust in health facilities and increase the number of cataract surgeries. It has been proven that since being implemented, the number of cataract surgeries has continued to increase, marked by an increase in cataract surgical rates (CSR) year by year: 2019 (921 CSR); 2020 (1401 CSR); 2021 (2628 CSR). This allows Jeneponto district to gradually get out from the red zone of blindness. Conclusion : Social media is a powerful tool to increase cataract awareness and public trust, especially during Covid-19 pandemic.